DOES CSR AND YOUNG BOARD DIRECTOR INFLUENCE THE PRACTICE OF TAX AGGRESSIVENESS? - Alfandy Berniquezt Dendeng; Vita Elisa Fitriana (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
This research aims to prove empirically the influence of corporate social responsibility and young board of director towards tax aggressiveness. The sample that used in this study is 60 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. This research using multiple linear regression analysis method. The result of this research indicates that corporate social responsibility has a significant influence towards the tax aggressiveness. Meanwhile, young board director do not have a significant influence towards the tax aggressiveness of the company. This result correlate with previous research that the higher corporate social responsibility disclosed indicates the higher tax aggressiveness conducted by the company.